A Perspective on Developing a Plant ‘Holobiont’ for Future Saline Agriculture - Ren, Cheng-Gang; Kong, Cun-Cui; Liu, Zheng-Yi; Zhong, Zhi-Hai; Yang, Jian-Chao; Wang, Xiao-Li; Qin, Song (Frontiers in Microbiology, 2022)
Soil salinization adversely affects plant growth and has become a major limiting factor for agricultural development worldwide. There is continuing demand for sustainable technology innovation in saline agriculture. Among various bio-techniques being used to reduce the salinity hazard, symbiotic microorganisms such as rhizobia and arbuscular mycorrhizal (AM) fungi have proved to be efficient. These symbiotic associations each deploy an array of well-tuned mechanisms to provide salinity tolerance for the plant. In this review, we first comprehensively cover major research advances in symbiont-induced salinity tolerance in plants. Second, we describe the common signaling process used by legumes to control symbiosis establishment with rhizobia and AM fungi. Multi-omics technologies have enabled us to identify and characterize more genes involved in symbiosis, and eventually map out the key signaling pathways. These developments have laid the foundation for technological innovations that use symbiotic microorganisms to improve crop salt tolerance on a larger scale. Thus, with the aim of better utilizing symbiotic microorganisms in saline agriculture, we propose the possibility of developing non-legume ‘holobionts’ by taking advantage of newly developed genome editing technology. This will open a new avenue for capitalizing on symbiotic microorganisms to enhance plant saline tolerance for increased sustainability and yields in saline agriculture.